2008
DOI: 10.1007/s10549-008-0221-0
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species induce phosphorylation of serine 118 and 167 on estrogen receptor alpha

Abstract: Estrogen receptor alpha (ERalpha) is a well-known target for signaling pathways originating from growth factor receptors. Reactive oxygen species (ROS) can induce activation of extracellular response kinase 1/2 (Erk1/2) and protein kinase B (Akt). Both kinases have been implicated in the phosphorylation of serine 118 and serine 167 on ERalpha, respectively. This activity may lead either to ligand-independent activation of ERalpha or down-regulation of ERalpha and may contribute to development of the resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…In the attempt to reveal the molecular mechanism underlying ROS-dependent GI mRNA downregulation, ER α and ERK1/2 signalling were studied. In fact, it has been shown that ROS can induce post-translational Erk1/2-dependent phosphorylation of ER α at serine 118, leading to ER α downregulation in MCF-7 (Weitsman et al , 2009). Moreover, we previously found that oestrogens positively modulated GI transcript levels in MCF-7 cell, possibly through the interaction of their receptors with degenerated ERE motives, identified in GI promoter by bioinformatics methods (Rulli et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the attempt to reveal the molecular mechanism underlying ROS-dependent GI mRNA downregulation, ER α and ERK1/2 signalling were studied. In fact, it has been shown that ROS can induce post-translational Erk1/2-dependent phosphorylation of ER α at serine 118, leading to ER α downregulation in MCF-7 (Weitsman et al , 2009). Moreover, we previously found that oestrogens positively modulated GI transcript levels in MCF-7 cell, possibly through the interaction of their receptors with degenerated ERE motives, identified in GI promoter by bioinformatics methods (Rulli et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…As ROS and AKT are involved in breast cancer metastasis [37,47,48], environmental forces for tumor development and metastasis may modulate ROS and AKT in cancer cells, vice versa . Meanwhile, ROS appears to force endocrine therapy resistance as well as tumorigenicity in ER + breast cancer, as glucose oxidase-mediated ROS induction led to the phosphorylation and downregulation of ERα in MCF-7 [42,49]. Likewise, ROS appears to regulate both the growth and invasiveness of TNBC cells [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…ROS has been shown to induce post-translational modifications of ER-α, leading to ER-α downregulation in human breast cancer cells. 30 Scavenging free radicals by NAC removed inhibitory effects of ROS, allowing steroid hormones to upregulate K Ca channel function. Correspondingly, BK Ca channel activity in uterine arterial smooth muscle cells was also restored by NAC with the hormonal treatment.…”
Section: Discussionmentioning
confidence: 99%